The Effects of Tax Avoidance, Accrual Earnings Management, Real Earnings Management, and Capital Intensity on the Cost of Equity (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2018)
This study aims to analyze the influence of PROPER Rating, Industrial Type, Profitability, Leverage and Age of Company on Carbon Emission Disclosure. Measurement of carbon emissions disclosure uses Carbon Emission Disclosure Checklist (CED). The population of this study is non-financial companies listed on the Indonesia Stock Exchange in 2013 - 2016 as many as 406 companies. The technique used in sampling is purposive sampling and selected 32 companies as sample and 126 units of analysis. The analytical tool used to test the hypothesis is descriptive statistical analysis and multiple linear regression analysis processed through IBM SPSS 21 program. The research results show that the PROPER rating and the type of industry have positive effect on carbon emission disclosure. While profitability, leverage and age of the company have no effect on carbon emission disclosure. The conclusions of this study are the PROPER rating and the type of industry proven to influence the company’s decision making to disclose carbon emissions. While the profitability, leverage, and firm age cannot affect the company’s decision to disclose carbon emissions.